2003
DOI: 10.1097/01.asn.0000056188.23717.e5
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Calcimimetics on Progression of Renal Failure and Cardiovascular Risk Factors

Abstract: Abstract. In renal failure, parathyroid hormone (PTH) is not only involved in the genesis of disturbed calcium/phosphate metabolism and ostitis fibrosa; it is also a permissive factor in the genesis of hypertension, cardiovascular damage, and dyslipidemia. The allosteric activator of the calcium sensing receptor NPSR-568 (R-568) has been shown to reduce the serum intact PTH (iPTH) concentration in uremic rats. It was the purpose of this study in subtotally nephrectomized (SNX) rats to compare pharmacologic abr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
96
2
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(109 citation statements)
references
References 59 publications
(67 reference statements)
9
96
2
2
Order By: Relevance
“…A delayed and less intense rise of albumin excretion was achieved with R-568 and calcitriol, consistent with previous findings in experimental studies (17,19) and clinical observations (2).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A delayed and less intense rise of albumin excretion was achieved with R-568 and calcitriol, consistent with previous findings in experimental studies (17,19) and clinical observations (2).…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, in this model, Ogata et al (17) showed that the effects of the calcimimetic agent and parathyroidectomy are comparable.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…When these effects are reversed, renal function may deteriorate acutely. In the long term, however, these hemodynamic changes may attenuate progression of renal failure as was shown in an animal model [50]. Overall, there appears to be no difference in the overall graft survival between patients who underwent PTX between 1966 and 1997 [51] and those who did so later [47,52].…”
Section: Surgical Concepts In Renal Hyperparathyroidismmentioning
confidence: 81%
“…13 These small compounds allosterically modulate the CaSR, making it more responsive to Ca 2 þ . The beneficial effects of calcimimetics on heart morphology, comparable with that of parathyroidectomy, were earlier suggested by a study in experimental uremia, 14 but no information is available on cardiac function and signaling pathways. We have shown earlier that the calcimimetic R-568 decreases albuminuria in subtotally nephrectomized rats.…”
mentioning
confidence: 95%